Online Reviews as Marketing Communications and Impact on Aloha Pantai Indah Kapuk - Murhadi, Murhadi; Putri Liqwiyanti, Mutiara Chaerany; Wiweka, Kadek (Bina Nusantara University, 2026)
This research examines the extent to which online reviews influence tourists’ decisions to visit Aloha PIK tourist attractions. Reviews from visitors, in both text and visual forms, serve as a source of information that greatly influences prospective tourists’ perceptions and decisions. This research uses a quantitative method with a sample of 100 Aloha PIK visitors and collects data through an online questionnaire. Based on the test results using simple linear regression, the t-count (15.831) is greater than the t-table value (1.984), and the significance value is 0.000 < 0.05. These results show that the independent variable has a significant effect on the dependent variable. In addition, the coefficient of determination (R²) of 0.719 indicates that the research model explains 71.9% of the variance, with the remaining 28.1% attributable to factors outside the model. In conclusion, 71.9% of respondents are influenced by online reviews in their decision to visit Aloha PIK. These findings confirm that managing digital reviews should be an integral part of a tourist destination’s marketing communication strategy. The implications of this research suggest that tourist destination managers should actively monitor, respond to, and manage online reviews as part of their digital marketing strategy. Positive reviews strengthen the destination’s image and encourage interest in visiting, while negative reviews require a measured response to avoid eroding potential tourists’ trust.